Химия и технология сероуглерода - Пеликс А. А. Александр Абрамович; Котомкина Р. Т. Рита Васильевна; Петров Е. А. Евгений Александрович; Аранович Б. С. Борис Семенович (Ленинград, Химия, 1986)
Авт. указаны на обороте тит. л.